Navigating Neurotrauma Management in Pakistan - Unaiza Naeem; Areesha Jawed; Alleza Jawed (Journal of the Pakistan Medical Association, 2022)
Madam, neurotrauma is defined as an injury to the brain and/or spinal cord. A WHO, sponsored study estimated that the annual global incidence of neurotrauma is approximately 500–800 per 100 000 and it accounts for about 11.8% of total global disability-adjusted life years1. In Pakistan, the annual incidence of head injured patients admitted to numerous neurosurgical centres was 50/100,000 population per year2. The lifetime medical treatment per neurotrauma case is estimated to range from US$600 000 to US$1.8 million. Neurotrauma management incorporates prehospital care lasting minutes to hours which encompasses accurate on site diagnosis and systematic treatment or during the e shifting, to an organized, well-equipped health care management, in-hospital care for hours to weeks which comprises surgical and non-surgical intervention including imaging, neuro-monitoring and critical care and finally post-acute care lasting weeks to years and denotes any form of rehabilitative interventions to enable and empower patients to have an increased quality of life1. Each component of management requires trained personnel, specific equipment, and protocols3. However, Pakistan lags in various aspects. As of a last study in 2001, there were only 35 neurosurgical centres and about 1000 neurosurgical beds to accommodate a population of 130 million2. Of the 23 Karachi hospitals studied in 2020, only 57% were well-equipped and accredited [Trauma capacity score (TCS) 67%] to perform elementary resuscitation steps to secure early stability. A sizeable number,57%, s (TCS<34%) lacked space to accommodate head, neck, and spinal injuries; 65% s were partly inadequate (TCS<67%) in diagnosis, intensive care and safety4. With low medical insurance across the country2. Inadequate availability of essential medicines was also reported in 43% of hospitals4. An organized trauma care system must be introduced to mitigate trauma mortality for local needs. It should encompass enabling those at injury site to become first responders3, an ambulance service equipped with communication systems and with properly trained personnel that can commence life-saving measures such as IV fluid resuscitation3. Trauma centres should have a referral network and hospitals that provide optimal traumatic care should be identified beforehand to transfer injured patients to this specialized facilitys4.A protocol also needs to be established that assists local doctors in immediate referral to trauma centers3. Proper allocation of resources and mobilization of staff and doctors timely can improve neurotrauma outcomes significantly. Continuous...